2015
DOI: 10.1016/j.hrtlng.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial edema in Takotsubo syndrome mimicking apical hypertrophic cardiomyopathy: An insight into diagnosis by cardiovascular magnetic resonance

Abstract: Myocardial edema is one of the characteristic features in the pathogenesis of Takotsubo syndrome. We report a middle aged man who presented with typical clinical and echocardiographic features of apical variant of Takotsubo syndrome. However, a cardiovascular magnetic resonance study performed 10 days after presentation did not show any apical 'ballooning' but revealed features of an apical hypertrophic cardiomyopathy on cine images. Tissue characterization with T2 weighted images proved severe edema as the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Sachdeva et al showed that an experimental model of Takotsubo cardiomyopathy presents persistent foci of necrosis and fibrosis [4]. Izgi et al reported myocardial edema as one of the characteristic features in the pathogenesis of Takotsubo syndrome [5]. Although the patient in our case study showed signs of Takotsubo cardiomyopathy, the endomyocardial biopsy of the LV did not show necrosis and the cardiac MRI did not demonstrate myocardial edema like in Takotsubo cardiomyopathy.…”
Section: Discussionmentioning
confidence: 49%
“…Sachdeva et al showed that an experimental model of Takotsubo cardiomyopathy presents persistent foci of necrosis and fibrosis [4]. Izgi et al reported myocardial edema as one of the characteristic features in the pathogenesis of Takotsubo syndrome [5]. Although the patient in our case study showed signs of Takotsubo cardiomyopathy, the endomyocardial biopsy of the LV did not show necrosis and the cardiac MRI did not demonstrate myocardial edema like in Takotsubo cardiomyopathy.…”
Section: Discussionmentioning
confidence: 49%
“…As previously mentioned, during the acute phase of SCM it is challenging to differentiate the two entities, especially the apical variant of HCM, since in those cases the disease process may be entirely masked by apical thinning or aneurysm caused by the SCM (Roy et al, 2014). The clinical scenario is further confounded in that there have been reports of a recently detected phenomenon of apparent left ventricular apical hypertrophy seen during the subacute and chronic phases of a resolving SCM, in patients without apical HCM (Izgi et al, 2015). In these circumstances the apical hypertrophy is due to transient myocardial edema, which can be detected utilizing cardiovascular magnetic resonance imaging (Izgi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, catecholamines may cause toxic myocarditis in cases of phaeocromocytoma 45,51 or stress-induced (Takotsubo) cardiomyopathy due to an exaggerated sympathetic stimulation. 52 Takotsubo cardiomyopathy is a transient left ventricular dysfunction most frequently characterized by an apical "ballooning" phenotype in people, 27,52,53 but myocardial edema mimicking HCM has also been described in Takotsubo cases, and differentiation from true HCM requires advanced cross-sectional imaging. [20][21][22][23]27,54 TMT could then potentially be caused by an emotional or physical stress associated with the reported antecedent events.…”
Section: Discussionmentioning
confidence: 99%
“…Transient myocardial thickening (TMT) mimicking HCM has been described in some forms of acute/fulminant myocarditis in humans and in atypical cases of stress‐induced (Takotsubo) cardiomyopathy . In both situations, the increased LVWT is associated with myocardial edema …”
mentioning
confidence: 99%
See 1 more Smart Citation